Difficulties Experienced by Older Listeners in Utilizing Voice Cues for Speaker Discrimination - Zaltz, Yael; Kishon-Rabin, Liat (Frontiers in Psychology, 2022)
Human listeners are assumed to apply different strategies to improve speech recognition in background noise. Young listeners with normal hearing (NH), e.g., have been shown to follow the voice of a particular speaker based on the fundamental (F0) and formant frequencies, which are both influenced by the gender, age, and size of the speaker. However, the auditory and cognitive processes that underlie the extraction and discrimination of these voice cues across speakers may be subject to age-related decline. The present study aimed to examine the utilization of F0 and formant cues for voice discrimination (VD) in older adults with hearing expected for their age. Difference limens (DLs) for VD were estimated in 15 healthy older adults (65–78 years old) and 35 young adults (18–35 years old) using only F0 cues, only formant frequency cues, and a combination of F0 + formant frequencies. A three-alternative forced-choice paradigm with an adaptive-tracking threshold-seeking procedure was used. Wechsler backward digit span test was used as a measure of auditory working memory. Trail Making Test (TMT) was used to provide cognitive information reflecting a combined effect of processing speed, mental flexibility, and executive control abilities. The results showed that (a) the mean VD thresholds of the older adults were poorer than those of the young adults for all voice cues, although larger variability was observed among the older listeners; (b) both age groups found the formant cues more beneficial for VD, compared to the F0 cues, and the combined (F0 + formant) cues resulted in better thresholds, compared to each cue separately; (c) significant associations were found for the older adults in the combined F0+formant condition between VD and TMT scores, and between VD and hearing sensitivity, supporting the notion that a decline with age in both top-down and bottom-up mechanisms may hamper the ability of older adults to discriminate between voices. The present findings suggest that older listeners may have difficulty following the voice of a specific speaker and thus implementing doing so as a strategy for listening amid noise. This may contribute to understanding their reported difficulty listening in adverse conditions.